Digitalization application in crowdfunding: A systematic review - Nurul Aien, Abd Aziz; Noraina Mazuin, Sapuan; Puteri Fadzline, Muhamad Tamyez; Neng Kamarni, . (Akademi Baru, 2026)
The digitalization of crowdfunding has reshaped the fundraising landscape, revolutionizing how projects and ventures secure financial support. This transformation has brought forward innovative platforms, altered user engagement and redefined the dynamics of financial inclusion. Digitalization in crowdfunding has expedited procedures and increased fundraising efforts that change the financial landscape. The purpose of this article is to provide a comprehensive review of the current body of knowledge about the digitalization of crowdfunding. The PRISMA approach was used to analyse an extensive compilation of empirical papers regarding the digitalization of crowd fundraising. These articles were obtained from the Scopus and Web of Science (WoS) databases using a search string of relevant keywords. A screening process was conducted to assess the eligibility of these articles, resulting in a total of 30 articles that were deemed fit for further analysis. The findings revealed three key themes concerning digitalization in crowdfunding research: (1) crowdfunding models and adoption, (2) technology and entrepreneurial financing and (3) social and cultural influences on crowdfunding. This study sheds light on the complicated interaction between blockchain, fintech and crowdfunding by investigating the dramatic implications of digitalization on crowdfunding dynamics. Crowdfunding also has prominent impacts on venture capital investments, China's dynamic digital finance ecosystem and Malaysian public schools' investment intents. Additionally, factors like trust, social effect and effort expectation are highlighted in the study, thus informing future crowdfunding techniques and platform operations in advancing financial technology and crowdfunding.